Seismic Behavior of Steel-Fiber-Reinforced High-Strength Concrete Shear Wall with CFST Columns: Experimental Investigation - Ke Shi (MDPI AG, 2021)
To improve the seismic behavior of shear walls, a new composite shear wall composed of a steel-fiber-reinforced high-strength concrete (SFRHC) web and two square concrete-filled steel tube (CFST) columns, namely a steel-fiber-reinforced concrete shear wall with CFST columns, is proposed in this paper. Therefore, the main purpose of this paper is to present an experimental investigation of the seismic behavior of the SFRHC shear wall with CFST columns. Pseudo-static tests were carried out on seven composite shear walls, and the seismic performance of the shear walls was studied and quantified in terms of the aspects of energy consumption, ductility and stiffness degradation. Furthermore, the experimental results indicated that adding steel fiber can effectively restrain the crack propagation of composite shear walls and further help to improve the ductility and energy dissipation capacity of composite shear walls and delay the degradation of their lateral stiffness and force. Moreover, the seismic behavior of the SFRHC shear wall with CFST columns was obviously superior to that of the conventionally reinforced shear wall, in terms of load-bearing capacity, ductility, stiffness and energy dissipation capacity, because of the confinement effect of the CFST columns on the web. Finally, the preliminary study demonstrated that the composite shear wall has good potential to be used in regions with high seismic risk.